Asymbiotic germination of the White Mountain Orchid (Pseudorchis albida) from immature seed on media enriched with complex organics or phytohormones - S. Pierce; B. E. L. Cerabolini (Seed Science and Technology, 2011)
The arctic-alpine White Mountain Orchid (Pseudorchis albida) has so-far resisted attempts at in vitro reproduction from seed, but a practical method is required for its conservation. We hypothesised that, having similar seeds to the notoriously intractable orchid Cypripedium calceolus, immature seeds can germinate in vitro. We collected mature and immature seeds from the Italian Alps, and sowed these in sterile conditions on Malmgren's basal nutrient medium modified with either phytohormones or complex organic media (COM). Different COM treatments included coconut milk, banana powder, malt extract and yeast extract, all at a concentration of 5%. Phytohormones, all at 20 mg L -1, included 6-benzylaminopurine (BA), gibberellic acid (GA 3), kinetin and thidiazuron (TDZ), added to autoclaved growth media via filter sterilization. After six months we found absolutely no germination of mature seeds for any treatment. Only 3.9% of immature seeds germinated in the control treatment and germination in all COM treatments was not significantly greater than this. However, most phytohormones significantly increased germination of immature seed and promoted protocorm development, BA being most effective (50.5% germination) - this method can therefore be used to propagate the species.